A Novel Therapy for Laryngotracheal Stenosis: Treatment With Ethosomes Containing 5-Fluorouracil. (July 2015) - Gu, Jian; Mao, Xiaohui; Li, Cong; Ao, Huafei; Yang, Xizhi
Purpose: The purpose of our article was to explore the effect of ethosomes containing 5-fluorouracil (5-FU) with different sizes on laryngotracheal stenosis treatment. Methods: The physical characteristics of ethosomes containing 5-FU were investigated, including size, shape, and entrapment percentage. The effect of ethosomes containing 5-FU was evaluated on the airway stenosis rabbit model. The formation of fibrous/scar tissue was investigated by hematoxylin and eosin (HE) staining, and the permeation depth was observed under fluorescence microscope. Results: The mean sizes of 5-FU ethosomes extruded by D = 50 nm and D = 100 nm pore were 60 ± 10 nm and 110 ± 13 nm, respectively. The 5-FU entrapment percentage of ethosomes was determined to be 15% (D = 60 ± 10 nm) and 32% (D = 110 ± 13 nm). After being treated by ethosomes containing 5-FU (D = 60 ± 10 nm), the fibroblast and collagenous fiber distributed sparsely in the deep scar tissue. The permeation capability of ethosomes containing 5-FU (D = 60 nm) was significantly better than ethosomes (D = 110 nm). Besides, the 5-FU ethosomes resulted in less stenosis than 5-FU only. Conclusions: Topical administration of 5-FU ethosomes may be a novel candidate therapy for laryngotracheal stenosis treatment.